2017
DOI: 10.3390/technologies5010009
|View full text |Cite
|
Sign up to set email alerts
|

In-Built Customised Mechanical Failure of 316L Components Fabricated Using Selective Laser Melting

Abstract: Abstract:The layer-by-layer building methodology used within the powder bed process of Selective Laser Melting facilitates control over the degree of melting achieved at every layer. This control can be used to manipulate levels of porosity within each layer, effecting resultant mechanical properties. If specifically controlled, it has the potential to enable customisation of mechanical properties or design of in-built locations of mechanical fracture through strategic void placement across a component, enabli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Pohl et al (Ref 10 ) reported lower deformation for higher scan speed. Combined effect of varying power and exposure together keeping energy density constant on porosity and in turn on mechanical properties was studied by Andrei et al (Ref 28 ). For a constant energy density, lower power and higher exposure combination led to an increase in porosity and thus reduction in yield strength of 316L SLM samples (Ref 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pohl et al (Ref 10 ) reported lower deformation for higher scan speed. Combined effect of varying power and exposure together keeping energy density constant on porosity and in turn on mechanical properties was studied by Andrei et al (Ref 28 ). For a constant energy density, lower power and higher exposure combination led to an increase in porosity and thus reduction in yield strength of 316L SLM samples (Ref 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen in Fig. 13a that most of the selected samples showed a~0.2 φ cross-micro (99.8% density) similar to conventional 316L stainless steel SLM parts [13]. The slower 1 mm/s scan speed showed a stable trend of low φ cross-micro whilst the higher 3 mm/s scan speed showed a high rate of decreasing φ cross-micro from~1.4 to~0.2% at increasing laser power.…”
Section: Cross-sectional Densitymentioning
confidence: 82%
“…This can be attributed to the continuous overlapping of laser spots creating a continuous melting area comprised by smaller melting spots. However, Ilie et al [13] report that porosity in stainless steel samples can vary when varying laser power or scanning velocity at same energy densities due to lack of fusion, Rayleigh instability, balling or poor wetting characteristics as detailed by Rombouts et al [14]. Decreasing levels of porosity were observed for LBP2 when scanned at 1 mm/s compared to the higher laser traversing speeds of 3 and 5 mm/s.…”
Section: Effect Of Powder Bed Characteristics On Response Trendsmentioning
confidence: 99%
“…Higher scan speed leads to increased cooling rate and increased cracking [32], while Pohl et al [24] reported lower deformation for higher scan speed. Lower power and higher exposure combination (for constant energy density) lead to increased porosity and thus reduced yield strength in 316-L SLM samples [33]. Ali et al [34] reported lower residual stress for lower power and higher exposure combination (for constant energy density).…”
Section: Slm Residual Stress Reductionmentioning
confidence: 99%